Synergic effect of compositions and processing method on the performance of high strength alkali activated slag foam. (17th October 2022) - Feng, Weipeng; Jin, Yu; Zheng, Dapeng; Li, Zheng; Cui, Hongzhi
Highlights: Mixing time was proved to effectively regulate the workability of AAS foam slurry. A model correlating compressive strength and geometrical information was proposed. The heat transfer behavior of AAS foam concrete was identified to be like dry sand. Abstract: Using inorganic porous materials for the insulation of a building improves energy efficiency. Alkali activated slag (AAS) foam concrete with a lower carbon footprint presents to be an alternative to cement-based foam concrete. In this study, the influence of various preparation parameters of AAS foam concrete on setting time, workability, compressive strength, bulk density, drying shrinkage and pore structure were investigated. A modified model was proposed to fit the relationship between compressive strength and geometrical information. Existing six structural models were used for the analytical description of the relationship between thermal conductivity and total porosity. Results show that increasing the mixing time can effectively extend the setting time and improve the workability of AAS foam slurry. The optimized mix proportion of AAS foam concrete exhibited a compressive strength of 24.1 MPa, thermal conductivity of 0.2322 W/(m·K) and adjustable setting time and workability for on-site casting. According to the comparison of the fitting results with other models, the proposed modified model for the relationship between compressive strength and geometrical information provided a better correlation with the experimental data. Analysis of the six structural models for the thermal conductivity showed that AAS foam concrete in this study favored the gaseous phase for heat transfer similar to the characteristic of dry sand.